Jews and the new American scene - Lipset, Seymour Martin 1922-2006; Raab, Earl (Harvard Univ. Press, 1995)
The authors vividly illustrate this paradox as it is experienced by American Jews today - in their high rates of intermarriage, their waning observance of religious rites, their extraordinary academic and professional success, their commitment to liberalism in domestic politics, and their steadfast defense of Israel. Yet Jews view these trends with a sense of foreboding: "We feel very comfortable in America - but anti-Semitism is a serious problem"; "We would be desolate if Israel were lost - but we don't feel as close to that country as we used to"; "More of our youth are seeking some serious form of Jewish affirmation and involvement but more of them are slipping away from Jewish life." These are the contradictions tormenting American Jews as they struggle anew with the never-dying problem of Jewish continuity